Sejarah Kerajaan Anas Pada Masa Pemerintahan Raja Leu Nesnay I Pada Tahun 1879-1908 - Tabala, Dorkas Novalia Maria; _, Djakariah; Utomo, Susilo Setyo (Universitas Nusa Cendana, 2023)
This research aims to examine the history of the Anas Kingdom before 1879 and to explore the economic, social, and political conditions during the reign of King Leu Nesnay I (1879-1908). The method used is historical with a qualitative approach, located in the former territory of the Anas Kingdom centered in the village of Lilo. (1) The research findings reveal that the Kingdom of Anas was established in the 16th century with its territory including Putain, Ukbui, Bimanus, Tauanas, Fatululi, Fatuoni, Sono, Sapnala, and Lotas. This kingdom was founded by Tae Nesnay from Belu (2) In the political field, King Leu Nesnay I managed the government with an organizational structure consisting of halamananu, halpala, amaf, mnaiskuan. In the social sphere, cooperation among neighboring kingdoms was implemented. Economically, the people of the Anas Kingdom were encouraged to engage in plantation and livestock sectors